EVALUATION OF TWO METHODS, CONVENTIONAL SCRAPING AND STRIPPING, FOR DIAGNOSIS OF DERMATOPHYTOSIS - M. Moghaddami; Sh. Hakim (Tehran University of Medical Sciences, 1995)
In a study of 310 patients with suspected dermatophytic lesions, 110 cases of dermatophytosis, were diagnosed by direct smear in 10% KOH and culture by two methods, skin stripping with use of adhesive tape and scrapping with scalpel blade conventional technique). Out of 65 positive cultures, in 33 cases, growth was obtained by methods (scraping and stripping), 23 by the conventional technique and 9 cases with the use of scotch tape only.